Nobody! : a story about overcoming bullying in schools - Frankel, Erin.; Heaphy, Paula (Minneapolis, MN : Free Spirit Pub., 2015)
In school Kyle's persistent bullying is making Thomas feel like a nobody, and he needs help from his classmates and adults to understand and recapture his self-esteem, but Kyle needs help too.
Includes activities for children and information on recognizing and preventing bullying for adults.
2
Keywords: Bullying in schools -- Juvenile fiction; Self-esteem -- Juvenile fiction; Bullying -- Fiction; Self-esteem -- Fiction; Schools -- Fiction; Bullies -- Fiction; Self-esteem -- Fiction; School stories